Plan estratégico de marketing para incentivar el turismo hacia los senderos interpretativos ubicados en la ruta del spondylus pertenecientes a la provincia de Santa Elena - Ramirez, E. (2009)
This paper proposes a strategic marketing plan to encourage tourism to the trails located in the communes of the province of Santa Elena, commune Dos Mangas: path "Las Cascadas" y "Las Pozas", commune Loma Alta: path "El Chorrillo" y "La Bramona", commune Salanguillo: path "Salto Chico" y "Las Campanas", commune Sinchal: path "Sinchal", commune La Entrada: path "La Entrada", commune Sacachun: path "Circulo de Piedras".. " The project basis to determine whether these pathways are tourists not operable with a promotion plan which set the target of the product, which provides incentives to tourists to visit the trails, in addition to proposing the appropriate promotion strategy, which is a system in which he emphasized the achievement of specific objectives which are to promote the image trails as a tourist destination, making positioning strategies that place in the national and international markets to Ecuador as alternative tourism and nature, by promoting trails of eco tourism, implementing matrices to formulate the marketing mix to the Top of Mind levels of consumers (PIMTE 2003) tourism is an activity multiplier of others.